Oxidative stress and its contribution to chronic periodontal inflammation - Albalbisi, Ayman M.; Asiri, Moahmmed S.; Alshahrani, Noura F.; Alqhtani, Saleh A.; Alqahtani, Saleh S.; Alqahtani, Shahd A.; Alnasrallah, Abdulkarim A.; Alqhatani, Aliya S.; Alasmari, Hassan G.; Jiffry, Hadeel A.; Alqahtani, Mohammed S. (International Journal Of Community Medicine And Public Health, 2025)
Periodontal disease is a group of diseases that affect the tissues that support the teeth. It is among the most prevalent oral diseases worldwide. Various mechanisms contribute to the pathogenesis of chronic periodontal inflammation, including oxidative stress. Oxidative stress leads to the production of reactive oxygen species (ROS), both exacerbating inflammatory reactions and worsening the health of gums and surrounding tissues, thus increasing disease severity. In addition, oxidative stress is a key factor mediating the influence of periodontitis on systemic diseases. However, the role of oxidative stress in the pathogenesis of chronic periodontal inflammation is unclear. This review aims to discuss the mechanisms through which oxidative stress contributes to chronic periodontal inflammation. Chronic periodontitis leads to continuous activation of polymorphonuclear neutrophils, which may be hyperactivated, resulting in overproduction of ROS and exacerbation of oxidative stress. Oxidative stress results in intracellular damage of proteins, lipids, and DNA, along with connective tissue destruction and bone resorption. Oxidative stress biomarkers, such as malondialdehyde and hydrogen peroxide, are closely linked to the development and severity of periodontitis. Antioxidants, such as vitamin C, vitamin E, and glutathione, can play a key role in the prevention and treatment of chronic inflammatory diseases, including periodontitis. Periodontitis also contributes to systemic diseases, such as cardiovascular diseases, diabetes mellitus, chronic kidney diseases, and liver diseases, via mechanisms, including systemic inflammation and oxidative stress. Future research should focus on clarifying oxidative stress molecular pathways in chronic periodontal disease, improving antioxidant-based therapies, and integrating personalized approaches through genomics and biomarkers.